Longitudinal monitoring of immunoglobulin A glycosylation during pregnancy by simultaneous MALDI-FTICR-MS analysis of N- and O-glycopeptides - Bondt, Albert (Sci Rep, 2016)
Immunoglobulin A (IgA) is a glycoprotein of which altered glycosylation has been associated with several pathologies. Conventional methods for IgA N- and O-glycosylation analysis are tedious, thus limiting such analyses to small sample sizes. Here we present a high-throughput strategy for the simultaneous analysis of serum-derived IgA1 N- and O-glycopeptides using matrix-assisted laser/desorption ionisation Fourier transform ion cyclotron resonance (MALDI-FTICR) mass spectrometry (MS). Six non-fucosylated diantennary complex type glycoforms were detected on the Asn144-containing glycopeptide. Thirteen distinct glycoforms were identified for the Asn340-containing tailpiece glycopeptide, mainly of the diantennary complex type, and low amounts of triantennary glycoforms. Simultaneously with these N-glycopeptides, 53 compositional glycoforms of the hinge region O-glycopeptide were profiled in a single high resolution MALDI-FTICR spectrum. Since many pregnancy associated changes have been recognized for immunoglobulin G, we sought to demonstrate the clinical applicability of this method in a cohort of 29 pregnant women, from whom samples were collected at three time points during pregnancy and three time points after delivery. Pregnancy associated changes of N-glycan bisection were different for IgA1 as compared to IgG-Fc described earlier. We foresee further applications of the developed method for larger patient cohorts to study IgA N- and O-glycosylation changes in pathologies.